SIGNIFYING THE SIGNS IN BREAKUPS OF A COUPLE OF LOVERS IN SIX SELECTED BATAK TOBA SONGS - Veronika Silalahi, Pininta (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
This study is intended to investigate the interpretant of five selected Batak Toba Songs about breaking the promise which causes breakup of love relationship. The research question is answered by applying Pierce's theory of signs or semiotics. It is used as the theoretical framework to show the relationship between the Object (Referent), Representation (words), and Interpretant, also known as the (reference). The object of the song is the brekup, the representamen is the lyrics of the five songs. The lyrics of these five songs are examined using semiotic analysis, and the meaning is interpreted based on Ogden and Richard's semantic triangle (1946). The finding shows there are nine signs of Interpretant found in the lyrics, they are heartbroken, sadness, loyalty, curse, profanity, sweet memory, gratuitous act and despair. It shows that there are some specific vocabulary in Batak language, like ripur, malengleng, matapor, magargar, etc.